Focusing on Increasing Velocity during Heavy Resistance Knee Flexion Exercise Boosts Hamstring Muscle Activity in Chronic Stroke Patients - Jonas Vinstrup; Joaquin Calatayud; Markus D. Jakobsen; Emil Sundstrup; Lars L. Andersen (Neurology Research International)
Background. Muscle strength is markedly reduced in stroke patients, which has negative implications for functional capacity and work ability. Different types of feedback during strength training exercises may alter neuromuscular activity and functional gains. Objective. To compare levels of muscle activity during conditions of blindfolding and intended high contraction speed with a normal condition of high-intensity knee flexions. Methods. Eighteen patients performed unilateral machine knee flexions with a 10-repetition maximum load. Surface electromyography (EMG) was recorded from the quadrics and hamstring muscles and normalized to maximal EMG (nEMG) of the nonparetic limb. Results. For the paretic leg, the speed condition showed higher values of muscle activity compared with the normal and blindfolded conditions for both biceps femoris and semitendinosus. Likewise, the speed condition showed higher co-contraction values compared with the normal and blindfolded conditions for the vastus lateralis. No differences were observed between exercise conditions for the nonparetic leg. Conclusion. Chronic stroke patients are capable of performing heavy resistance training with intended high speed of contraction. Focusing on speed during the concentric phase elicited higher levels of muscle activity of the hamstrings compared to normal and blindfolded conditions, which may have implications for regaining fast muscle strength in stroke survivors.